EFEKTIFITAS LKPD BERBASIS INKUIRI TERBIMBING PADA MATERI GARIS SINGGUNG LINGKARAN KELAS VIII - Sari, Intan Permata; Maulidiya, Della; Susanta, Agus (JP2MS, 2021)
This research was done to produce student worksheet (LKPD) based on inquiry on tangent line to a cirle for grade 8 that is effective. This research was a Research and Development by modifying 4-D thiagarajan method into 3 phases of it, which are define, design, and develop. The effectiveness of LKPD was done to 32 students of Class VIII A in SMP Negeri 11, Bengkulu city as an effective class and was observed by two observers. Instrument of this research was effective sheet consist of teacher activity observation sheet, sudent activity observation sheet and student’s response sheet. The result of this research showed that LKPD was in effective category based on : 1) teacher activity observation that consisted of 8 statements was in very good category with an average score 34,5;  2) student activity observation that consisted of 7 statements was in very good category with an average score 30,17;  3) student’s response that consist of 10 statements was in very good category with an average score 43,76; and 4) learning outcome of students based on score of LKPD and Final Test (THB) was in good category with classical mastery persentage up to 93,75%.